1999
DOI: 10.1097/00004872-199917110-00013
|View full text |Cite
|
Sign up to set email alerts
|

Influence of demographic, anthropometric and lifestyle characteristics on heart rate and its variability in the population

Abstract: Age, gender and/or some lifestyle factors significantly affect heart rate and various components of its variability in the supine position and in response to standing. The results are similar for autoregressive modelling and fast Fourier transform, but may differ according to the units in which the spectral components are expressed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
45
2
1

Year Published

2004
2004
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 90 publications
(62 citation statements)
references
References 32 publications
14
45
2
1
Order By: Relevance
“…Consequently, there were higher LF/HF ratio values in the standing position than in the supine position. This stimulation of sympathetic nervous system modulation in response to postural change has also been observed in other studies on different populations (22,32,33).…”
Section: Position Effectsupporting
confidence: 86%
See 1 more Smart Citation
“…Consequently, there were higher LF/HF ratio values in the standing position than in the supine position. This stimulation of sympathetic nervous system modulation in response to postural change has also been observed in other studies on different populations (22,32,33).…”
Section: Position Effectsupporting
confidence: 86%
“…the standing position in the women's group, indicating a reduction of parasympathetic modulation caused by the postural change maneuver in female subjects. Fagard et al (32) also found a reduction in vagal modulation evident in decreased HF indexes; however, the reduction occurred in both genders and not only in women, as observed in the present study. Nevertheless, these investigators evaluated a wide age range (from 25 to 89 years), which might have been responsible for the differences in results between the two studies.…”
Section: Position Effectsupporting
confidence: 60%
“…However, Hoikuri et al investigated subjects that were middle-aged 24) . The lower LF/HF ratio was also observed in women at young age in comparison with men 25) . Bigger et al reported that men had higher LF and VLF parameters than women 26) .…”
Section: Discussionmentioning
confidence: 70%
“…Leuven. The sampling unit consisted of randomly recruited households in a Flemish rural area in Belgium [5,12] and of nuclear families in the other centres [13]. The study was approved by the ethics committee of each centre and the subjects gave informed consent.…”
Section: Study Populationmentioning
confidence: 99%